Nutritional Programming of Accelerated Puberty in Heifers: Involvement of Pro‐Opiomelanocortin Neurones in the Arcuate Nucleus. (August 2015) - Cardoso, R. C.; Alves, B. R. C.; Sharpton, S. M.; Williams, G. L.; Amstalden, M.
<x xml:space="preserve">Abstract</x> The timing of puberty and subsequent fertility in female mammals are dependent on the integration of metabolic signals by the hypothalamus. Pro‐opiomelanocortin (POMC) neurones in the arcuate nucleus (ARC) comprise a critical metabolic‐sensing pathway controlling the reproductive neuroendocrine axis. α‐Melanocyte‐stimulating hormone (αMSH), a product of the POMC gene, has excitatory effects on gonadotrophin‐releasing hormone (GnRH) neurones and fibres containing αMSH project to GnRH and kisspeptin neurones. Because kisspeptin is a potent stimulator of GnRH release, αMSH may also stimulate GnRH secretion indirectly via kisspeptin neurones. In the present work, we report studies conducted in young female cattle (heifers) aiming to determine whether increased nutrient intake during the juvenile period (4–8 months of age), a strategy previously shown to advance puberty, alters POMC and KISS1 mRNA expression, as well as αMSH close contacts on GnRH and kisspeptin neurones. In Experiment 1, POMC mRNA expression, detected by in situ hybridisation, was greater (P < 0.05) in the ARC in heifers that gained 1 kg/day of body weight (high‐gain, HG; n = 6) compared to heifers that gained 0.5 kg/day (low‐gain, LG; n = 5). The number of KISS1‐expressing cells in the middle ARC was reduced (P < 0.05) in HG compared to LG heifers. In Experiment 2, double‐immunofluorescence showed limited αMSH‐positive close contacts on GnRH neurones, and the magnitude of these inputs was not influenced by nutritional status. Conversely, a large number of kisspeptin‐immunoreactive cells in the ARC were observed in close proximity to αMSH‐containing varicosities. Furthermore, HG heifers (n = 5) exhibited a greater (P < 0.05) percentage of kisspeptin neurones in direct apposition to αMSH fibres and an increased (P < 0.05) number of αMSH close contacts per kisspeptin cell compared to LG heifers (n = 6). These results indicate that the POMC‐kisspeptin pathway may be important in mediating the nutritional acceleration of puberty in heifers.